Implementation of Blockchain Smart Contract for Online Concert Ticket Transactions Based on NFTs - Lingga Pratyaksa Nugraha, Anak Agung; Emmy Rosiana Dewi , Ni Wayan; Purnama, Fajar (Politeknik Negeri Batam, 2025)
The development of the entertainment industry, especially music concerts, has driven the transformation of ticket sales systems from conventional to digital methods. Although online concert ticket sales offer greater convenience and reach, they still face the risks of fraud, counterfeit tickets, and unfair distribution. This study, Blockchain Smart Contract Implementation for NFT-Based Online Music Concert Ticket Transactions, aims to develop a ticket sales system using blockchain technology by integrating smart contracts and Non-Fungible Tokens (NFTs). The main objectives are to design and implement smart contracts on the Ethereum network, implement ERC-721-based digital tickets, ensure transparency in transaction history, and verify ticket authenticity through unique identifiers. This study adopts the Agile method, with implementation on the Ethereum Sepolia Testnet and testing using the meta mask digital wallet. The results show that the developed system can automatically hold funds through an escrow mechanism until the ticket is downloaded, generate unique and tamper-proof NFT tickets, display transaction details transparently, and facilitate ticket verification effectively. In conclusion, the use of smart contracts and NFTs significantly improves the security, transparency, and trustworthiness of online music concert ticket transactions.